Quantifying immediate and delayed effects of anthelmintic exposure on ecosystem functioning supported by a common dung beetle species - Manning, P; Beynon, S; Lewis, O (Public Library of Science, 2017)
Dung beetles (Coleoptera: Scarabaeoidea) support numerous ecosystem functions in livestock-grazed pastures. Exposure to veterinary anthelmintic residues in livestock dung can have lethal and sublethal effects on dung beetles, and can reduce rates of dung removal, but the immediate and longer-term consequences for other dung beetle mediated functions have rarely been studied. We investigated the consequences of anthelmintic exposure on survival of the dung beetle Aphodius fossor and its delivery of four ecosystems functions that underpin pasture production: dung removal, soil fauna feeding activity, primary productivity, and reduction of soil compaction. We tested whether anthelmintic exposure had immediate or delayed effects on these functions individually and simultaneously (i.e., ecosystem multifunctionality). We found no evidence that ivermectin residues had a lethal effect on adult beetles. For dung removal, we found a significant interaction between the timing of exposure and functioning: while dung removal was impaired by concurrent exposure to high levels of ivermectin, functioning was unaffected when beetles that had been exposed previously to the same concentration of anthelmintic later interacted with untreated dung. Other ecosystem functions were not affected significantly by anthelmintic exposure, and there was no evidence to suggest any persistent impact of anthelmintic exposure on ecosystem multifunctionality. While anthelmintic residues remain a significant threat to dung beetle populations, for adult beetles, we found no evidence that residues have detrimental consequences for ecosystem functioning beyond the immediate point of exposure.